CULTURE-CENTRED DIGITAL DESIGN: FOREGROUNDING CHILDREN AND YOUNG PEOPLE’S PERSPECTIVES - Third, Amanda; Welland, Louisa Amanda; Pathak Shelat, Manisha; Shah, Vama; Lala, Girish; Moody, Lilly; Haryana, Diena (AoIR Selected Papers of Internet Research, 2026)
This pilot study employed a decolonised, youth-centred methodology to challenge dominant discourses and hierarchies in knowledge production. The Distributed Data Generation (DDG) approach facilitated participatory workshops across Australia, India, and Indonesia, involving collaboration with local research centres and a youth organisation. This cross-cultural partnership aimed to unsettle Western assumptions about research methodologies and knowledge representation. DDG prioritises marginalised perspectives and has been used to collaborate with global South organisations for rights-based youth research. It enables rich data collection through participatory, child-centred workshops conducted simultaneously in multiple countries. This approach supports the decolonisation of youth knowledge by co-producing it with children and young people, addressing child-adult power imbalances. The research engaged 128 participants aged 9 to 18 from diverse backgrounds, including urban and rural areas, culturally and linguistically diverse communities, migrants, and disadvantaged youth. Each participant attended a workshop to explore cultural expressions, ethics, responsibilities, and aspirations for culture-centred digital design. Findings reveal that digital technology influences and shapes the cultural practices of young people in Australia, India, and Indonesia. Indian participants view culture through nationalism and ideology, while Australian children associate culture with material practices and the environment. Digital technologies were found to strengthen cultural identity and cross-cultural understanding, though concerns about minority culture representation were expressed. Indian and Indonesian youth use digital platforms to learn about their own and other cultures, more so than Australian participants. Concerns about cultural exclusion, inappropriate content, and digital disharmony were highlighted, emphasising the need for inclusive digital design that reflects the lived experiences of diverse youth.